The Aarhus Chamber Campaign on Highly Oxygenated Organic Molecules and Aerosols (ACCHA): particle formation, organic acids, and dimer esters from α-pinene ozonolysis at different temperatures - K. Kristensen; L. N. Jensen; L. L. J. Quéléver; S. Christiansen; B. Rosati; B. Rosati; J. Elm; R. Teiwes; H. B. Pedersen; M. Glasius; M. Ehn; M. Bilde (Atmospheric Chemistry and Physics, 2020)
Little is known about the effects of subzero temperatures on the formation of secondary organic aerosol (SOA) from α-pinene. In the current work, ozone-initiated oxidation of α-pinene at initial concentrations of 10 and 50 ppb, respectively, is performed at temperatures of 20, 0, and −15 ∘C in the Aarhus University Research on Aerosol (AURA) smog chamber during the Aarhus Chamber Campaign on Highly Oxygenated Organic Molecules and Aerosols (ACCHA). Herein, we show how temperature influences the formation and chemical composition of α-pinene-derived SOA with a specific focus on the formation of organic acids and dimer esters. With respect to particle formation, the results show significant increase in particle-formation rates, particle number concentrations, and particle mass concentrations at low temperatures. In particular, the number concentrations of sub-10 nm particles were significantly increased at the lower 0 and −15 ∘C temperatures. Temperature also affects the chemical composition of formed SOA. Here, detailed offline chemical analyses show that organic acids contribute from 15 % to 30 % by mass, with highest contributions observed at the lowest temperatures, indicative of enhanced condensation of these semivolatile species. In comparison, a total of 30 identified dimer esters were seen to contribute between 4 % and 11 % to the total SOA mass. No significant differences in the chemical composition (i.e. organic acids and dimer esters) of the α-pinene-derived SOA particles are observed between experiments performed at 10 and 50 ppb initial α-pinene concentrations, thus suggesting a higher influence of reaction temperature compared to that of α-pinene loading on the SOA chemical composition. Interestingly, the effect of temperature on the formation of dimer esters differs between the individual species. The formation of less oxidized dimer esters – with oxygen-to-carbon ratio (O:C)<0.4<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="58pt" height="12pt" class="svg-formula" dspmath="mathimg" md5hash="b1929e0a2ba3da80b926f1257f0caf6b"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-20-12549-2020-ie00001.svg" width="58pt" height="12pt" src="acp-20-12549-2020-ie00001.png"/></svg:svg> – is shown to increase at low temperatures, while the formation of the more oxidized species (O:C>0.4<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="54pt" height="10pt" class="svg-formula" dspmath="mathimg" md5hash="80d0320197869a61867471b61880bfb4"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-20-12549-2020-ie00002.svg" width="54pt" height="10pt" src="acp-20-12549-2020-ie00002.png"/></svg:svg>) is suppressed, consequently resulting in temperature-modulated composition of the α-pinene-derived SOA. Temperature ramping experiments exposing α-pinene-derived SOA to changing temperatures (heating and cooling) reveal that the chemical composition of the SOA with respect to dimer esters is governed almost solely by the temperature at which oxidization started and is insusceptible to subsequent changes in temperature. Similarly, the resulting SOA mass concentrations were found to be more influenced by the initial α-pinene oxidation temperatures, thus suggesting that the formation conditions to a large extent govern the type of SOA formed, rather than the conditions to which the SOA is later exposed. For the first time, we discuss the relation between the identified dimer ester and the highly oxygenated organic molecules (HOMs) measured by chemical ionization–atmospheric pressure interface–time-of-flight mass spectrometer (CI-APi-ToF) during the ACCHA experiments. We propose that, although very different in chemical structures and O:C ratios, many dimer esters and HOMs may be linked through similar RO2 reaction pathways and that dimer esters and HOMs merely represent two different fates of the RO2 radicals.